Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/aelm.201700026
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Carrier Density of SrTiO3‐Based Heterostructures with Annealing

Abstract: Abstract:The conducting interface between the insulating oxides LaAlO3 (LAO) and SrTiO3 (STO) displays numerous physical phenomena that can be tuned by varying the carrier density, which is generally achieved by electrostatic gating or adjustment of growth parameters. Here, we report how annealing in oxygen at low temperatures ( < 300 ℃) can be used as a simple route to control the carrier density by several orders of magnitude. The pathway to control the carrier density relies on donor oxidation and is thus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 41 publications
3
57
0
Order By: Relevance
“…3(b)], hence suggesting a favored formation of type B oxygen vacancies and/or diffusion of vacancies from the bulk to the interface. A recent annealing study of γ-Al 2 O 3 /SrTiO 3 indeed identified such diffusion processes, in support of the mechanism proposed here [45]. Figure 4(a) schematically summarizes our experimental and theoretical findings.…”
supporting
confidence: 87%
“…3(b)], hence suggesting a favored formation of type B oxygen vacancies and/or diffusion of vacancies from the bulk to the interface. A recent annealing study of γ-Al 2 O 3 /SrTiO 3 indeed identified such diffusion processes, in support of the mechanism proposed here [45]. Figure 4(a) schematically summarizes our experimental and theoretical findings.…”
supporting
confidence: 87%
“…The case of GAO/STO with a GAO film thicker than 1–2 nm is particularly interesting, as the conductivity here is stable at room temperature on the time scale of years at ambient conditions, but by elevating the temperature to 200–300 °C the conductivity could be tuned to a desired level . This is depicted in Figure where GAO was deposited by PLD at an oxygen partial pressure of 10 −5 mbar resulting in an initial sheet carrier density of around 2 × 10 14 cm −2 .…”
Section: Other Factors: Adsorbates Particle Bombardment and Temperamentioning
confidence: 99%
“…The transport properties and interface conductivity of STO‐based heterostructures can be readily tuned by varying the deposition conditions during the growth of the top oxide thin film . With the notable exception of interface conductivity originating from oxygen vacancies in STO, the conducting properties of STO‐based heterostructures are generally very stable. However, it is possible to electrostatically modulate the interfacial properties of STO‐based heterostructures by applying an external electric field using a gate.…”
Section: Electrostatic Potentialmentioning
confidence: 99%
See 2 more Smart Citations